Manajemen Program BPI (Bina Pribadi Islam) dalam Membentuk Akhlak Peserta Didik di SMP IT Al-Hijrah - Soraya, Intan; Daulay, Nurika Khalila; Tarigan, Mardinal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was motivated by the researcher's interest in the Islamic Personal Development program at SMP IT Al-Hijrah which in fact is the flagship program of the JSIT curriculum (Integrated Islamic School Network) which is able to shape students' Islamic personalities. The purpose of this study is to identify the management of the Islamic Personal Development program in shaping the morals of students in SMP IT Al-Hijrah starting from the planning, organizing, implementing and supervision stages. The method used in this study is qualitative with a phenomenological approach with data collection techniques, namely observation, interviews, and documentation. The results of the study are (1) BPI program planning in shaping the morals of students at SMP IT Al-Hijrah including setting goals, forming organizational structures and tasks, schedules, materials as well as grouping students and assessments. (2) The organization of the BPI program is carried out by forming an organizational structure along with its role. (3) The implementation of the BPI (Bina Pribadi Islam) Program in shaping the morals of students at SMP IT Al-Hijrah is carried out in groups in accordance with BPI rules every Monday from 07.00-10.00 WIB. (4) Supervision of the BPI (Bina Pribadi Islam) program in shaping the morals of students at SMP IT Al-Hijrah is carried out by monitoring, reporting, follow-up, assessment and evaluation. Based on the findings of the research above, the Management of the Islamic Personal Development Program in shaping the morals of students at Al-Hijrah IT Junior High School is that it has succeeded in shaping the morals of students but has not been maximized. Factors that influence the inadequacy of this program are Human Resources or BPI (Bina Pribadi Islam) Coaches that do not yet fully exist, lack of parental control at home, lack of innovation or new ideas in BPI management.